In situ characterization of ceramic cold sintering by small‐angle scattering. Issue 6 (1st February 2021) - Allen, Andrew J.; Levin, Igor; Maier, Russell A.; Witt, Suzanne E.; Zhang, Fan; Kuzmenko, Ivan
Abstract: The first in situ characterization of the pore morphology evolution during the cold sintering process (CSP) is presented using small‐angle X‐ray scattering methods. For practical reasons, measurements have been made on a model system, KH2 PO4 (KDP). The scattering signal revealed a striking behavior that could be modeled with nanoscale structural features associated with the dissolution and reprecipitation of KDP close to the grain/pore interface during CSP. The prospects for future more quantitative experiments under a range of temperature and pressure conditions, as well as for studies of more technologically important materials such as ZnO are considered.